A practical approach for gmp-compliant validation of real-time PCR method for mycoplasma detection in human mesenchymal stromal cells as advanced therapy medicinal product. (September 2021) - Becherucci, V.; Curini, L.; Ceccantini, R.; Bisin, S.; Gori, V.; Gentile, F.; De Rienzo, E.; Piccini, L.; Bindi, B.; Pavan, P.; Cunial, V.; Allegro, E.; et al.
Abstract: Background: Manufacturing of human Mesenchymal Stromal Cells as advanced therapy medicinal product (ATMP) for clinical use involves an ex vivo expansion, which leads to a risk of contamination by microbiological agents. Even if manufacturing under Good Manufacturing Practice (GMP) license minimizes this risk, contamination of cell cultures by mycoplasmas still represents a widespread problem. Furthermore, the absence of mycoplasma contamination represents one of ATMPs release criteria. Since July 2007, European Pharmacopoeia (EuPh) offers the possibility to replace official mycoplasma detection methods with Nucleic Acid Amplification techniques, after suitable validation. As an Italian authorized Cell Factory, we developed an in-house GMP-compliant validation of real-time PCR method for mycoplasma detection in human Mesenchymal Stromal Cells, according to EuPh sec. 2.6.7 and International Conference on Harmonization Q2 . Materials and methods: The study was performed in compliance with GMP international requirements with MycoSEQ™ Mycoplasma Detection Assay ( Thermofisher ) on QuantStudio5 real-Time PCR ( Applied Biosystems ). Assay validation was developed to evaluate sensitivity, interferences matrix-related, specificity and robustness. Results: MycoSEQ™ Mycoplasma Detection Assay has been successfully validated on human Mesenchymal Stromal Cells as results comply with validation protocol acceptance criteria. Conclusions: MycoSEQ™ Mycoplasma Detection Assay is a fast, sensitive and specific PCR-based Nucleic Acid Test assay that can be used as an alternative to official mycoplasma test methods for lot release of human Mesenchymal Stromal Cells as advanced therapy medicinal product (ATMP). Moreover, our study underlines the presence of interference on real-time PCR reaction due to matrix composition, pointing out a practical approach for method validation ( i.e interference removal).